TAWURAN PELAJAR DALAM PERSPEKTIF KRIMINOLOGIS, HUKUM PIDANA, DAN PENDIDIKAN - Anjari, Warih (MAJALAH ILMIAH WIDYA, 2012)
The phenomenon of student disturb should be paid fully attention from all parties and society . Students will be the next generationto decide the nationâs future. The students are in the education process which their mind set should contain morality and knowledge.The purpose of this paper is to find out: (1) the students disturb causes, (2) the law effect, (3) the perspective of education. The methodused library research and the data analyzed descriptively. It is concluded that: (1) the violence was caused of direct effect from disturbs,with the subject and certain motive which the target subject are students and the certain motive is the admission. (2) The studentâscase is applied to âPasal 170 KUHPâ, (3) It is needed to work on the process of education from all parties and society to make aconducive situation. (4) The studentâs case must be handles comprehensively from the sociology, psychology and cultural point ofview.